2021
DOI: 10.1371/journal.pone.0250367
|View full text |Cite
|
Sign up to set email alerts
|

Institutional injustice: Implications for system transformation emerging from the mental health recovery narratives of people experiencing marginalisation

Abstract: Background Institutional injustice refers to structures that create disparities in resources, opportunities and representation. Marginalised people experience institutional injustice, inequalities and discrimination through intersecting personal characteristics and social circumstances. This study aimed to investigate sources of institutional injustice and their effects on marginalised people with experience of mental health problems. Methods Semi-structured interviews were conducted with 77 individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…The findings highlight that Black and Afro-Caribbean people have continued to be disproportionately over-represented in mental health services and that mental health services are not meeting their needs (HM Government, 2018). BME people are likely to experience multiple forms of disadvantage relating to mental health, educational attainment and socio-economic status (Hui et al , 2021). Furthermore, BME people have been experiencing higher rates and frequencies of being sectioned, secluded and restrained and have been more likely to access mental health services via the criminal justice system (Wessely et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The findings highlight that Black and Afro-Caribbean people have continued to be disproportionately over-represented in mental health services and that mental health services are not meeting their needs (HM Government, 2018). BME people are likely to experience multiple forms of disadvantage relating to mental health, educational attainment and socio-economic status (Hui et al , 2021). Furthermore, BME people have been experiencing higher rates and frequencies of being sectioned, secluded and restrained and have been more likely to access mental health services via the criminal justice system (Wessely et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interviews were conducted primarily to inform the development of conceptual frameworks describing recovery narratives and their impact, with the objectives of (1) accessing the recovery stories of a diverse population, and (2) exploring positive and negative impacts of accessing other people's stories. Findings on this data have been published elsewhere (Hui et al, 2021;Llewellyn-Beardsley et al, 2020;Slade et al, 2019). A secondary aim was to explore people's experiences of how they told their stories in various settings, and these experiences are reported here.…”
Section: Research Contextmentioning
confidence: 97%
“…People who experience mental distress experience injustice when their identities are devalued through the acquisition of psychiatric diagnoses which in turn leads to stigmatization (Harper & Speed 2014). Institutional structures create injustice where there are disparities in resources, opportunities, and representation between majority and non-majority perspectives, for example, inequalities in access to treatment, experiences of health services, and treatment outcomes (Hui et al 2021). It occurs when treatment or services cause harm, even when the professed intentions underpinning the institution are benevolent.…”
Section: Recovery And/or Psychiatric Discoursementioning
confidence: 99%
“…It occurs when a person's treatment preferences are dismissed because the psychiatric diagnosis attributed to that person suggests an inability to think rationally or clearly (Kurs & Grinspoon 2018). In the face of this institutional injustice, it has been suggested that at the clinician level approaches are needed to avoid two related dangers: diagnostic overshadowing in which a person's experiences and physical symptoms are misattributed to mental illness and granting master status to one aspect of a person's identity by disregarding other aspects (Hui et al 2021). Given the chasm of differences between recovery principles and psychiatric discourse and the injustices embedded, is it possible to build a bridge between the two?…”
Section: Recovery And/or Psychiatric Discoursementioning
confidence: 99%